Factors Affecting Serum 25-(OH)D Levels and Its Relation with Quality of Life: A Single-Center Study in a Sample of Turkish Postmenopausal Women - Ertuğrul, Ayşegül İlbaş and Cengiz, Mahir and Fenercioğlu, Ayşen and Koksal, Selçuk and Turfaner Sipahioğlu, Nurver (Cerrahpaşa Medical Journal, 2022)
Objective: We aimed to investigate the relationship of vitamin D levels, which gain more importance in postmenopausal women due to osteoporosis, with knowledge, physical and environmental factors, and quality of life. Methods: One hundred two postmenopausal women who applied to Istanbul University-Cerrahpasa, Cerrahpasa Medical Faculty, Family Medicine and Internal Medicine clinics between December 2017 and July 2018 were recruited for this study. Nottingham Health Profile and a questionnaire of 13 items about demographics and knowledge about vitamin D were applied face to face. The participants were separated into 3 groups: group 1. (25(OH) vitamin D level <20 ng/mL), vitamin D deficiency; group 2: (25(OH) vitamin D level 20.01-29.99 ng/mL), vitamin D insufficiency; and group 3: (25(OH) vitamin D level ≥30 ng/mL), normal vitamin D. Data were evaluated using Kolmogorov–Smirnov test, chi-square test, Fisher’s exact test, 1-way analysis of variance, and Kruskal–Wallis test. Results: There were 37 women (36.30%) in group 1, 27 women (26.50%) in group 2, and 38 women (37.30%) in group 3. Their median age was 55 (42-98) years and mean body mass index was 27.97 ± 4.96 kg/m2. Quality of life was not significantly different between the 3 groups (P > .05). Alcohol use, skin type, clothing style, and physical activity were significantly different between the 3 groups (P = .04, P = .013, P = .001, and P = .020). Better knowledge about 25(OH)D was related significantly to higher vitamin D levels (P < .05). Conclusion: Increasing physical activity and sunbathing with enough skin exposure should be recommended for postmenopausal women in order to augment plasma vitamin D levels. Cite this article as: İlbaş Ertuğrul A, Cengiz M, Fenercioğlu A, Koksal ,S, Turfaner Sipahioğlu N. Factors affecting serum 25-(OH)D levels and its relation with quality of life: A single-center study in a sample of turkish postmenopausal women. Cerrahpaşa Med J. 2022;46(2):129-133.